PERTANGGUNGJAWABAN SHOPEE KEPADA KONSUMEN TERHADAP PENYALAHGUNAAN FITUR KREDIT (PAY LATER) OLEH PIHAK KETIGA - Muhammad Ferdiansyah, (2024)
Fintech is a step-in renewal in the financial sector by utilizing technology. As regulated related to Fintech in the Financial Services Authority Regulation (POJK) Number 77/POJK.01/2016 concerning Loan Services Borrowing Money Based on Information Technology and Bank Indonesia Regulation (PBI) Number 19/12/PBI/2017 concerning the Implementation of Financial Technology, however the regulation only regulates how to work or stages of technology-based lending services with good and correct procedures. The rapid development of fintech in Indonesia unfortunately is not followed by extentive personal data protection. Indonesia does not yet have a special law in protecting personal data so that in the implementation of digital transactions, there are often many frauds by irresponsible parties. As happened to the NH who was a victim of the ShopeePayLater account abuse by a third party. The purpose of this study is to find out the legal protection of ShopeePayLater consumers who are victims of third parties and also know the responsibility of Shopee towards victims. This research method uses normative legal research, with the data collection method used in this study is a library study. Based on the results of this study, Shopee has carried out various security systems based on regulations related to personal data including Law Number 39 of 1999, Law Number 8 of 1999, Law Number 19 of 2016, Law Number 24 of 2013, Permen Kominfo Number 20 of 2016, PP Number 71 of 2019, PP Number 80 of 2019, and POJK Number 4/POJK.05/2021. Based on the explanation above, the party can still be said to not yet have a security system that is not fully safe, because there are still leaks of consumer personal data that can be misused.